Combined analysis of five non-interventional studies of the effectiveness, tolerability, and safety of the extrafine fixed dose beclomethasone/formoterol combination in the treatment of asthma in Austria. (February 2023) - Renner, A.; Marth, K.; Breyer-Kohansal, R.; Pohl, W.
Abstract: Objective: The real-world effectiveness and tolerability of an extrafine fixed dose beclomethasone/formoterol (BDP/FF) treatment of patients with partially or non-controlled asthma was evaluated in five non-interventional studies (NISs) from Austria. Methods: Asthma patients enrolled in these five NISs were treated with beclomethasone/formoterol (Foster® or Foster® Nexthaler®) as maintenance and reliever over 12 weeks. Asthma control, lung function and symptom scores were assessed at baseline, after 4–8 weeks and at the end of the investigations in week 12. In addition, tolerability and handling of the devices were evaluated by questionnaires. Results: The combined analysis included 891 patients (53% female, aged 49.3 years) demonstrating significant improvements in asthma control, lung function parameters (PEF, FEV1 and FVC) and symptom scores (reduction of breathlessness, wheezing, chest tightness and cough). These changes were already detectable after 4–8 weeks. The treatment was effective irrespective of smoking status, exercise, or previous medication. Tolerability of the therapy with extrafine BDP/FF was rated as "very good" or "good" in 98% of the patients. 95% of the patients intended to continue the treatment, and nearly all (99%) rated the handling of the device as "very good" or "good". No serious adverse reactions were reported. Conclusions: This combined analysis of five non-interventional studies confirms the effectiveness and tolerability of the extrafine fixed-dose BDP/FF combination (Foster® and Foster® Nexthaler®) in a heterogenous patient population suffering from partially or non-controlled asthma. Therapy was associated with a high patient satisfaction and the absence of serious adverse reactions. Highlights: Fixed dose extra fine beclomethasone/formoterol was effective in real world asthmatics, confirming observations from RCTs. It is effective and well tolerated in a heterogenous patient population suffering from partially or non-controlled asthma. Its application is associated with a high patient satisfaction and the absence of serious adverse reactions.